1998
DOI: 10.1021/js970462j
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Displacement by Rat Serum of Adsorbed Radiolabeled Poloxamer and Poloxamine Copolymers from Model and Biodegradable Nanospheres

Abstract: 0 Poloxamer 407 and poloxamine 908 have been used by many research groups to modify the surface of both model latex and biodegradable nanospheres, thereby producing nanospheres that have shown reduced protein adsorption in vitro and extended circulation times in vivo. A potential limitation of such systems is the desorption of the copolymer coating layer. We describe a two-stage process to radiolabel poloxamer 407 and poloxamine 908 that has facilitated an investigation into this potential desorption, in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Earlier work with radio-labeled poloxamine 908-coated (at plateau region of the adsorption isotherm) polystyrene nanoparticles (250 nm) demonstrated that not more than 10% of poloxamine molecules are released after 3 h incubation in serum. 31 With nanospheres C and D, this translates to less than 25 and 40 g poloxamine/mL serum, respectively, which is far below the minimum free poloxamine concentration necessary to trigger complement via the lectin pathway (Figure 5a). Therefore, nanosphere-mediated lectin pathway activation is likely due to interaction between MBL and/or ficolin with projected PEO chains, resulting in activation of their associated serine protease zymogen MASP-2.…”
Section: ϫ30mentioning
confidence: 97%
“…Earlier work with radio-labeled poloxamine 908-coated (at plateau region of the adsorption isotherm) polystyrene nanoparticles (250 nm) demonstrated that not more than 10% of poloxamine molecules are released after 3 h incubation in serum. 31 With nanospheres C and D, this translates to less than 25 and 40 g poloxamine/mL serum, respectively, which is far below the minimum free poloxamine concentration necessary to trigger complement via the lectin pathway (Figure 5a). Therefore, nanosphere-mediated lectin pathway activation is likely due to interaction between MBL and/or ficolin with projected PEO chains, resulting in activation of their associated serine protease zymogen MASP-2.…”
Section: ϫ30mentioning
confidence: 97%
“…In one study, PEGylated nanoparticles, 220 nm in diameter, were cleared faster from the body than those with 60 nm diameter [61]. In another study, three different sizes (80,170 and 240 nm) of nanoparticles were compared for serum protein adsorption and phagocytosis [62]. The results showed that particles with 80 nm exhibited only 6% opsonization whereas higher opsonization was found for lager particles (23% for 170 nm and 34% for 240 nm).…”
Section: Designing Long-circulating Nanoparticles 41 Sizementioning
confidence: 99%
“…Guidelines have also been proposed to optimize the thickness of the PEG layer to achieve stealth properties [79]. Care must also be taken to ensure that PEG does not desorb from the nanoparticles surface in the presence of competing molecules [80].…”
Section: Polyethylene Glycol (Peg)mentioning
confidence: 99%
“…These coatings can modify the biodistribution of NPs when injected into the systemic circulation. However, it has been argued that some of these polymers can be easily displaced by serum proteins, which can lead to aggregation of NPs [57]. Thus, alternative approaches of synthesizing co-polymers of PLA/PLGA with PEG [58,59] and co-encapsulation of PEG with plasmid DNA inside PLA NPs have been tried [60].…”
Section: Affecting Biodistribution Of Npsmentioning
confidence: 99%